Fifteen years of the master's degree in genetic counseling in Portugal: Are we heading in the right direction? - Moreira, Inês; Guimarães, Lídia; Paneque, Milena (Journal of Genetic Counseling, 2025)
Genetic counseling arose as a field in the late 1960s in the United States, with the creation of the first master's level degree. Since then, the profession has expanded globally, with several training degrees being established and genetic counselors integrated into national healthcare systems. In Portugal, though the profession is yet to be recognized, a master's degree in genetic counseling was established in 2009 at ICBAS (University of Porto). Fifteen years later, and with the everlasting progress in the genetics field, to investigate how to continue improving and advancing genetic counseling education in Portugal, a qualitative, exploratory study was designed. Fourteen supervisors from the second‐year annual placement of the MSc degree were invited to participate in semi‐structured interviews about their expectations and perceptions regarding the master's. Reflexive thematic analysis was used for the qualitative data gathered. Ten supervisors took part in this study, with 17 years as the average experience in the genetics field. Four key themes were constructed from the data. First, supervisors identified specific challenges in genetic counseling education, including limited infrastructure at host institutions—which restricts the type and depth of supervision that can be provided—and the need to adapt internship plans to students' diverse educational backgrounds. They also emphasized the importance of strengthening collaboration between educators and supervisors to ensure better alignment between academic preparation and practical training. The second theme centered on the experience of being a supervisor in the genetic counseling master's program. Supervisors' responses revealed diverse supervision styles and limited knowledge of the program's academic components. They also highlighted the students' motivating presence and the strong sense of purpose they felt when training new professionals. The third key theme concerned the integration of genetic counselors within genetic services. Supervisors acknowledged the added value genetic counselors bring to clinical settings, despite ongoing changes in service provision and limited career opportunities. The final theme related to misconceptions about the profession's scope of practice and training. This study provides insightful strategies to continue the development and improvement of the genetic counseling training in Portugal, and enhances the urgency of integrating these professionals into the healthcare system, with the ultimate purpose of promoting a more effective and comprehensive delivery of genetic counseling services in the country.